1995
DOI: 10.1007/bf00223902
|View full text |Cite
|
Sign up to set email alerts
|

The molecular cytogenetics of Vigna unguiculata (L.) Walp: the physical organization and characterization of 18s-5.8s-25s rRNA genes, 5s rRNA genes, telomere-like sequences, and a family of centromeric repetitive DNA sequences

Abstract: A knowledge of genome organization is important for understanding how genomes function and evolve, and provide information likely to be useful in plant breeding programmes involving hybridization and genetic manipulation. Molecular techniques, including in situ hybridization, molecular cloning and DNA sequencing, are proving valuable tools to investigate the structure, organization, and diversity of chromosomes in agricultural crops. Heterologous labelled 18 s-5.8 s-25 s (pTa71) and 5 s rDNAs (pTa794) were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
5

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 47 publications
5
36
0
5
Order By: Relevance
“…According to , the variation in the number of rDNA sites observed between species of related taxa could be due to the differ-ential amplification and fixation of rDNA sequences at different chromosomal sites. On the other hand, four 5S ribosomal sites were observed in V. radiata and V. unguiculata , confirming the previous reports for V. unguiculata (Galasso et al, 1995), although these reports were first published for V. radiata.…”
Section: Polytene Chromosomes Of Anther Tapetumsupporting
confidence: 88%
“…According to , the variation in the number of rDNA sites observed between species of related taxa could be due to the differ-ential amplification and fixation of rDNA sequences at different chromosomal sites. On the other hand, four 5S ribosomal sites were observed in V. radiata and V. unguiculata , confirming the previous reports for V. unguiculata (Galasso et al, 1995), although these reports were first published for V. radiata.…”
Section: Polytene Chromosomes Of Anther Tapetumsupporting
confidence: 88%
“…la) and in other six accessions (Table 1) showed the presence of three telomeric CMA + blocks per haploid genome on chromosomes named 2, 4, and 5 plus a block located at the secondary constriction of chromosome 3 following the numenclature of GALASSO et al (1993); chromosome 1, the most prominent chromosome of the complement, is also indicate in all pictures. All the accessions showing this pattern belonged to v. unguiculata subsp.…”
Section: Resultsmentioning
confidence: 75%
“…These signals were confirmed as bright spots in the interphase nuclei of H. catharinensis ( Figure 1C). Whereas the co-location of CMA 3 -positive bands with rDNA loci is common in Hypochaeris (Cerbah et al, 1998;Ruas et al, 2005) as well as in other plant groups (Galasso et al, 1995;Fukui and Nakayama, 1996;Vanzela et al, 2002), the unusual distribution of GC-rich heterochromatin identified in H. catharinensis differs from any pattern already described for other Hypochaeris species. Although we could not detect any AT-rich block in H. catharinensis, Reck et al (2011) described a DAPI fluorescent signal located at the intersticial position on short arms of chromosome pair 4 of this species.…”
Section: Chromosome Bandingmentioning
confidence: 68%